Estudo das propriedades eletrônicas e estruturais em nanotubos de fosfeto de índio - Coutinho, Jeferson (2009)
In this work, using first principles study based in framework of the density functional theory with the local density approximation (LDA) for the exchange-correlation functional, we developed a detailed study about the stability and the electronic properties of Indium Phosphite (InP) nanotubes. We use a plane wave basis set and to solve the standard Khon-Sham (KS) equations in a self consistent way we use the Viena Ab initio Simulation Package (VASP). Experimental works show that the InP nanotubes are synthesized using the vapor liquid solid (VLS) method and present the zinc blend structure with a wall thickness about 2 to 10 nm. Based on these experimental findings, the central objective of the work is the study of InP nanotubes with different wall thickness. To simulate the wall thickness, we use concentric single walled nanotubes th the In a P atoms arranged in a hexagonal structure. Also, zinc blend InP hollow nanowires were used. Firstly we checked the methodology by calculating the main properties of the InP in the bulk phase. We investigate the cohesion energy, lattice parameter, bulk modulus, etc. and compared our results with experimental data and others theoretical results using similar techniques. Once the methodology was checked we performed a detailed study of the Multi Walled InP nanotubes. We calculate the cohesion energy, formation energy, electronic band structure, electronic density of states, charge density, etc. Our result present that the InP nanotubes are metastable structures. The formation and cohessive energies decrease rapidly when we move from one to two walls and change in a sligtly way when the number of the walls continues to increase. Starting from a hollow nanowire or nanotubes with three and four single layer, we obtained similar formation and cohesion energy, however the geometry structure is a bit different. Furthermore we observed that the band gap of the single walled nanotube increase when the diameter decrease reveling quantum confinement effects. For nanotubes with more than one wall the semiconductor character is keeping. All the single wall InP nanotubes are semiconductor but the band gap present a dependence with the nanotube chirality.